2022
DOI: 10.1038/s41598-022-14964-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prognosis and clinical features of the tumor microenvironment based on ferroptosis score in patients with breast cancer

Abstract: Ferroptosis genes have recently been reported to be involved in regulating the development of cancer, but their potential role in breast cancer (BRCA) is not fully understood. The purpose of this study is to systematically study the mechanism of ferroptosis in BRCA and its relationship with this cancer’s prognosis, cell infiltration, gene mutation, and other clinical features. In this study, The Cancer Genome Atlas breast cancer (TCGA-BRCA) database (UCSC Xena) was used to mine the ferroptosis genes related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Long survival times have been achieved in BC, as the improvement of the comprehensive treatment of local recurrence or distant metastasis has become the main challenge for clinicians. Previous study has built a ferroptosis score model and showed a good predictive value for OS in BS patients [ 39 ]. In this study, a novel prognostic model for DFS combined with 6 FRGs was also established with the TCGA-BRCA training cohort and revealed a good predictive value of recurrence in internal and external validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Long survival times have been achieved in BC, as the improvement of the comprehensive treatment of local recurrence or distant metastasis has become the main challenge for clinicians. Previous study has built a ferroptosis score model and showed a good predictive value for OS in BS patients [ 39 ]. In this study, a novel prognostic model for DFS combined with 6 FRGs was also established with the TCGA-BRCA training cohort and revealed a good predictive value of recurrence in internal and external validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration curve con rmed its high predictive e cacy for 3-, and 5-year survival time. Recently, an 8 ferroptosis-genes prognostic model has been conducted for BRCA prognosis (24).Therefore, the ferroptosis score may be very helpful for us to predict the clinical outcome of patients. Cancer is a genetic disease associated with the accumulation of mutations (25).…”
Section: Discussionmentioning
confidence: 99%
“…At present, most chemotherapeutic drugs play a role by inducing tumor cell apoptosis. However, if the apoptosis of tumor cells fails, there will be chemotherapy resistance (24). Chemoresistance is a major obstacle to curing cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, principal component analysis (PCA) was performed to extract principal component 1 as the characteristic fraction. The ferroptosis score index for each sample was then calculated using a method similar to the gene expression rating as follows: ferroptosis score = ∑PC1B − ∑PC1A, where PC1A represents the first component of feature A, PC1B represents the first component of feature B, and the scores of ferroptosis modification patterns and genotyping were detected [ 28 ]. Use R software “ggalluvial” package to draw Sankey.…”
Section: Methodsmentioning
confidence: 99%